2019
DOI: 10.3897/zookeys.856.32017
|View full text |Cite
|
Sign up to set email alerts
|

An annotated checklist of the leaf beetles (Coleoptera, Chrysomelidae) from El Salvador, with additions from the Bechyné collection in the Royal Belgian Institute of Natural Sciences

Abstract: A checklist of the species of leaf beetles (Coleoptera: Chrysomelidae) of El Salvador is presented based on data from literature and a digitization project of the Bechyné collection of the Royal Belgian Institute of Natural Sciences (RBINS). The RBINS collections contain a total of 2797 individual chrysomelid specimens from El Salvador, sorted into 89 species and 132 genera. In total, the current checklist contains 420 species, of which 33 are new records for El Slavador from the Bechyné collection. In these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…While the validity of Chrysodinopsis remains unchallenged, both species should be placed in the same genus based on their morphological proximity; thus, we formalize the new combination here. Previously reported from El Salvador, Guatemala, Honduras, and Mexico (Flowers 1996 ; Van Roie et al 2019 ), the presence of C. cupriceps in Nicaragua would extent the range of the species considerably to the south. Nicaraguan specimens range from cupreous to metallic green, blue, purple, and almost black, sometimes with slight differences in the hue of pronotum and elytra, but the head is always of a different color compared to the rest of the body (Fig.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…While the validity of Chrysodinopsis remains unchallenged, both species should be placed in the same genus based on their morphological proximity; thus, we formalize the new combination here. Previously reported from El Salvador, Guatemala, Honduras, and Mexico (Flowers 1996 ; Van Roie et al 2019 ), the presence of C. cupriceps in Nicaragua would extent the range of the species considerably to the south. Nicaraguan specimens range from cupreous to metallic green, blue, purple, and almost black, sometimes with slight differences in the hue of pronotum and elytra, but the head is always of a different color compared to the rest of the body (Fig.…”
Section: Resultsmentioning
confidence: 79%
“…T. rugosus (Jacoby, 1882), described from Mexico, has been reported as a pest of different crops across Central America (e.g., Coto et al 1995 ), and there has been a trend to automatically refer all Talurus found attacking crops to this species, including in Nicaragua (e.g., Maes and Staines 1991 ). However, based on our assessment, all the available specimens of Talurus from Nicaragua, which display quite a range of chromatic alternatives, actually belong to T. tortonesei Bechyné, and perhaps other country records also need a reassessment (e.g., Van Roie et al 2019 ). Bechyné ( 1957 ) detailed the main differences between the two species, where the most remarkable would include the preapical enlargement of protibiae in T. tortonesei , against the straight tibiae of T. rugosus , but also the finer, denser punctation on pronotum and a less transverse pronotum in the case of T. tortonesei .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Blackwelder 's work (1946) documented the leaf beetles richness of several Central and South American countries; however, only Brazil (Costa, 2000), Chile (Elgueta & Arriagada, 1989), El Salvador (Van Roie et al, 2019), Nicaragua (Maes & Staines, 1991;Maes, Gómez-Zurita, Riley et al, 2016;Maes, Gómez-Zurita, & Staines, 2016), and Peru (Chaboo & Clark, 2015;Chaboo & Flowers, 2015a, 2015cChaboo & Morse, 2015;Chaboo & Schmitt, 2015;Chaboo & Staines, 2015;Furth et al, 2015) have updated their information (Table 3). According to these data, Mexican richness of leaf beetles known to date (332 genera, 2,556 species) is only exceeded by the Brazilian richness (364 genera, 4,486 species).…”
Section: Discussionmentioning
confidence: 99%
“…However, some coleopterists have collected in the country (e.g., Howden and Peck 1972;Ratcliffe and Cave 2006). Only two Coleoptera families have updated checklists for the country: Chrysomelidae with 420 species (Van Roie et al 2019) and Staphylinidae with 96 species (Pablo-Cea et al 2021). The only subfamily of Scarabaeidae that has been systematically studied in El Salvador is Dynastinae, with 65 species (Ratcliffe and Cave 2006).…”
Section: Introductionmentioning
confidence: 99%